PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN DISERTAI HANDOUT TERHADAP HASIL BELAJAR IPA SISWA KELAS VII MTSN TALAOK KAPUBATEN PESISIR SELATAN - Sari, Depi Aprila (STKIP PGRI Sumbar, 2014)
The problem in this is result of learning research biology classes VII MTsN Talaok are still low. Itâs solution is application of type cooperative learning model Round Robin and handout. The research purposed to know the effect of the application of type cooperative learning model Round Robin and handouts to result learning students of IPA class VII MTsN Talaok. The kind of research is Experiment. The research design used Randomized Control Group Posttest Only Design. This population of research are students of MTsN Talaok specially of VII classes IPA. Sampling by using purposive sampling technique. Experiment class is VII.4 class and control class is VII.6 class. The instrument used objective form with four option. Based on the data obtained average results of experiment class learning is 77.48, and the control class is 70.17. From analysis t-tes obtained t (1.72)> t table (1.67). It is concluded that learning Cooperative learning model type Round Robin and handout can improve learning result biology classes VII MTsN Talaok academic 2013/2014 years.